Answer:
( -1 , 26)
Explanation:
So since you need to find the other endpoint, you would follow these steps:
1.)
![4 = (9 + x)/(2\\)](https://img.qammunity.org/2021/formulas/mathematics/college/7azgejj1vx7agsn5dxwnsiymrlcubla996.png)
2.) 8 = 9 + x ( you just multiplied the 2 to the 4 to get 8)
3.) -1 = x (just solve it like a regular equation, so just subtract 9 on both sides to get rid of it and that leaves you with -1 = x)
You took the x values of both points and put them in the equation.
And its the same for y
1.)
![8 = (-10 + y)/(2)](https://img.qammunity.org/2021/formulas/mathematics/college/moyb5m0egl95dn14i64y2f7oxe48qmys8d.png)
2.) 16 = -10 + y
3.) 26 = y (you added the 10 on both sides because the 10 was negative and that took the 10 out and so it left you with 26 = y)